HOW FTA AND NAFTA TREATIES AFFECT THE BUSINESS CYCLES SYNCHRONIZATION BETWEEN THE U.S. AND CANADA - Živkov, Dejan; Malešević, Olja; Malešević, Žana; Malšević, Jovana (International Journal of Economic Practice and Policy, 2019)
This paper strives to gauge whether the introduction of Free Trade Agreement (FTA) and North American Free Trade Agreement (NAFTA) positively influenced business cycle synchronization between the U.S. and Canada. For computational purposes, we choose wavelet coherence and phase difference methodologies. Our results indicate that synchronization between cycles was realized much faster after the introduction of these treaties in ‘80s and ‘90s of the 20th century. Also, results show that synchronization is achieved faster in crisis (after two quarters), while in tranquil periods it takes little bit longer (three quarters). Phase difference suggests that the U.S.’s business cycle is one that leading.